239 The Use of the ASQ-3 as A Potential Developmental Screening Tool in an Irish Population. (October 2012) - Halling, C; Malone, F; Corcoran, D
Abstract : Background: The Bayley Scales of Infant and Toddler Development is a standardised developmental assessment that assesses children up to 42 months. The goal of the assessment is to identify those children with developmental delay. The Ages and Stages Questionnaire (ASQ-3) is a standardised developmental questionnaire that parents complete. The purpose of the questionnaire is to identify those children who warrant a more detailed developmental assessment such as The Bayley Scales Assessment. Aim: To assess the ASQ-3 for identification of children with developmental delay in an Irish population. Methods: A cohort of 87 pairs of twins (174 children) was taken from an on-going larger twin study. All children were assessed with both the ASQ-3 and The Bayley Scales Assessment. Results: In our cohort, the ASQ-3 has a sensitivity of 95% and a specificity of 57%. Although the ASQ-3 will give some false positive results, it is a good screening tool for picking up children with potential developmental delay as very few children with true delay will be missed. Discussion: Although The Bayley Scales Assessment is the gold standard for assesment of developmental delay, it is time consuming and must be carried out by a qualified professional. Only those at highest risk for developmental delay are therefore assessed. Our results suggest that the ASQ-3 can be used a screening tool in low risk populations to identify those children who may be at risk for developmental problems.